Diels–Alder Cycloaddition to the Bay Region of Perylene and Its Derivatives as an Attractive Strategy for PAH Core Expansion: Theoretical and Practical Aspects - Kurpanik, Aneta; Matussek, Marek; Lodowski, Piotr; Szafraniec-Gorol, Grażyna; Krompiec, Michał; Krompiec, Stanisław (Molecules (Basel, Switzerland), 2020)
PAHs (polycyclic aromatics hydrocarbons), the compound group that contains perylene and its derivatives, including functionalized ones, have attracted a great deal of interest in many fields of science and modern technology. This review presents all of the research devoted to modifications of PAHs that are realized via the Diels–Alder (DA) cycloaddition of various dienophiles to the bay regions of PAHs, leading to the π-extension of the starting molecule. This type of annulative π-extension (APEX) strategy has emerged as a powerful and efficient synthetic method for the construction of polycyclic aromatic hydrocarbons and their functionalized derivatives, nanographenes, and π-extended fused heteroarenes. Then, [4 + 2] cycloadditions of ethylenic dienophiles, -N=N-, i.e., diazo-dienophiles and acetylenic dienophiles, are presented. This subject is discussed from the organic synthesis point of view but supported by theoretical calculations. The possible applications of DA cycloaddition to PAH bay regions in various science and technology areas, and the prospects for the development of this synthetic method, are also discussed.